Future uncertainties for the distribution and conservation of Paubrasilia echinata under climate change - Esser, Luíz Fernando (2019)
Paubrasilia echinata is a widely cultivated endangered tree species with small populations restricted to a narrow strip of habitats along the Brazilian coast. The potential impacts of climate change on the distribution of P. echinata have yet to be investigated, and so it remains unknown whether protected areas will ensure the persistence of the species in the future. Here, we estimate the impacts of climate change on the distribution of P. echinata inside and outside of protected areas considering different climate change scenarios and two different sets of presence records: natural distribution and cultivated records. Future scenarios showed a gradual reduction in climatically suitable area both inside and outside of protected areas. Projections indicate a trend for a shift to the highlands of Southeast Brazil, and the loss of several areas throughout the entire distribution of the species. Predicted climatic conditions will be unsuitable for P. echinata inside most protected areas. Information provided here will be relevant in planning future national actions for this species, which is a must to properly protect this long-exploited tree.